2001
DOI: 10.1046/j.0962-1083.2001.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal by animals: exact identification of source trees with endocarp DNA microsatellites

Abstract: A long-standing challenge in studies of seed dispersal by animal frugivores has been the characterization of the spatial relationships between dispersed seeds and the maternal plants, i.e. the seed shadow. The difficulties to track unambiguously the origin of frugivore-dispersed seeds in natural communities has been considered an unavoidable limitation of the research field and precluded a robust analysis of the direct consequences of zoochory. Here we report that the multilocus genotype at simple sequence rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
277
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(287 citation statements)
references
References 43 publications
5
277
0
5
Order By: Relevance
“…Current modeling techniques, however, likely underestimate seed dispersal distances because they assume seeds in traps arrive from the nearest adult tree. Models also fail to adequately account for long-distance seed input that may play a substantial role in spatial genetic processes (Oddou-Muratorio et al, 2001), as well as individual variability in fecundity and survivorship (Godoy and Jordano, 2001). Perhaps most importantly for the present study, the current models fail to incorporate dioecy and thus underestimate seed dispersal because any reproductive size adult is considered a potential seed donor.…”
Section: Discussionmentioning
confidence: 82%
“…Current modeling techniques, however, likely underestimate seed dispersal distances because they assume seeds in traps arrive from the nearest adult tree. Models also fail to adequately account for long-distance seed input that may play a substantial role in spatial genetic processes (Oddou-Muratorio et al, 2001), as well as individual variability in fecundity and survivorship (Godoy and Jordano, 2001). Perhaps most importantly for the present study, the current models fail to incorporate dioecy and thus underestimate seed dispersal because any reproductive size adult is considered a potential seed donor.…”
Section: Discussionmentioning
confidence: 82%
“…This suggests that populations A and B were established by similar founding material and that subsequent geneflow into the two populations has been similar. Previous work in P. mahaleb indicated that the majority of seed dispersed beneath a maternal tree were its own progeny with up to 62% of seeds being delivered within 15 m of the source tree (Godoy and Jordano, 2001). Earlier studies in wild cherry also noted that the vast majority of wild cherry seed was dispersed no further than 50 m from the mother tree (Turcek, 1968).…”
Section: Discussionmentioning
confidence: 89%
“…However, in a Slovakian wild cherry population, isoenzyme polymorphism did reveal significant levels of SGS in the first distance class examined (o36.8 m) (Gö mö ry and Paule, 2001). Microsatellite or simple sequence repeat (SSR) markers are codominant and highly polymorphic and have been widely used in forest tree population studies over recent years (Godoy and Jordano, 2001;Asuka et al, 2004;Heuertz et al, 2004;Marquardt and Epperson, 2004). Recently, we have optimized a suite of SSR markers from P. avium to enable the efficient genotyping of wild cherry in population scale studies (Vaughan and Russell, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In temperate ecosystems, the main seed dispersers of fleshy-fruited trees are carnivorous mammals and birds (Guitián & Munilla, 2010;García et al, 2010;Peredo et al, 2013). Birds typically account for a large proportion of dispersed seeds (Jordano, 1987;Herrera, 1998;Martínez et al, 2008), depositing them at very short distances from mother trees (Godoy & Jordano, 2001;Jordano et al, 2007;Martínez et al, 2008), and usually under tree canopies as a result of their active selection of forest habitats (Alcántara et al, 2000;Jordano & Schupp, 2000;Martínez et al, 2008;Martínez & García, 2015a). This is the case of yew in the Cantabrian mountains (N Spain), for which birds tend to disproportionately disperse the seeds beneath conspecific adult trees (García et al, 2005b;Martínez et al, 2008), a pattern that may hamper recruitment due to increase predation, pathogen attack, and competition in high-density seed or seedling clumps (JanzenConnell effects;Janzen, 1970;Schupp & Jordano, 2011;Devaney et al, 2014).…”
Section: Study Species Taxus Baccata Lmentioning
confidence: 99%